Multi-mode resource constrained project scheduling under resource disruptions. (8th May 2016) - Chakrabortty, Ripon K.; Sarker, Ruhul A.; Essam, Daryl L.
Highlights: Formulated two discrete time based models to deal with disruption scenarios. A solution approach is proposed to generate a revised schedule after disruptions. Proposed recovery options show better performance than simple right shifting. This model is capable of dealing with a single, as well as multiple disruptions. Abstract: Over the last few decades, research on resource constrained project scheduling has focused on the development of mathematical programming based approaches for the generation of a nominal schedule under a deterministic environment. During the implementation phase, however, the nominal schedule may need to be revised when one or more resources are disrupted for a length of time. In this paper, we formulate two discrete time based models to deal with two different disruption scenarios for multi-mode resource constrained problems. We propose a reactive re-scheduling procedure for a single, as well as a series of disruptions, without having any disruption information in advance. To test the proposed approaches, sets of ten, twenty and thirty-activity multi-mode test instances from Project Scheduling Library (PSLIB) were used after introducing randomly generated disruption events. The experimental studies were also carried out to determine the effect of different factors related to the disruption recovery process.